Determination of NAD+ precursors nicotinamide mononucleotide (NMN) and nicotinamide riboside (NR) in plant foods: exploring dietary sources - Gabriela Fabiana Soares Alegre; Glaucia Maria Pastore (CyTA - Journal of Food)
NAD+ is vital for all living organisms, playing key roles in redox reactions and cellular signaling. Understanding the levels of its biosynthetic precursors, NMN and NR, in foods is essential for assessing their dietary contributions to human nutrition and health. We conducted a comprehensive analysis of NMN, NR, and NAD+ levels for the first time in various common plant foods and non-conventional food plants from the Amazon, using a validated HPLC-DAD/UV method, further confirmed by LC-MS/MS. NMN concentrations ranged from 40 to 13,000 µg per 100 g of fresh weight, while the NR levels varied from 62 to 1,600 µg per 100 g. Broccoli and green beans were identified as rich sources of NMN, whereas wild chicory, banana, and orange had the highest NR content. This study enhances our understanding of how to optimize NAD+ levels through dietary sources and advances knowledge in food science and nutrition.